The Effect of Attractiveness, Expertise, Visual Attractiveness and Interactivity on Online Impulsive Buying Behavior - Fajar, Faried; Bambang Widjanarko Otok (Jurnal Ilmiah Manajemen Kesatuan, 2024)
An innovative approach to product marketing through live streaming on TikTok can potentially encourage impulsive buying behavior among Indonesian customers, offering opportunities for e-commerce business owners to increase sales. This research focuses on identifying factors influencing impulsive purchasing decisions for fashion products through live streaming on TikTok, namely attractiveness, expertise, visual appeal, and interactivity. Using the Stimulus-Organism-Response (SOR) theoretical framework, this study explores consumer reactions and behaviors caused by stimulus factors which are then analyzed using Structural Equation Modeling (SEM) PLS techniques with the SmartPLS application based on 156 valid respondents on TikTok. The results are expected to guide fashion business actors in social commerce to design effective marketing strategies using TikTok live streaming by emphasizing aspects of perceived enjoyment to encourage impulse buying.